2009
DOI: 10.1073/pnas.0813257106
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic hybrid materials for constitutional self-instructed membranes

Abstract: Constitutional self-instructed membranes were developed and used for mimicking the adaptive structural functionality of natural ionchannel systems. These membranes are based on dynamic hybrid materials in which the functional self-organized macrocycles are reversibly connected with the inorganic silica through hydrophobic noncovalent interactions. Supramolecular columnar ion-channel architectures can be generated by reversible confinement within scaffolding hydrophobic silica mesopores. They can be structurall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 48 publications
2
68
0
Order By: Relevance
“…[25] Thetransport activity of 1a decreased in the following order: (Table 1), corresponding to the Eisenman sequence IV or V. [26] We know from previously reported X-ray single-crystal structures,t hat lipophilic ureido-benzo-15-crown-5-ether and ureido-benzo-18-crown-6-ether bind Na + (Figure 3a)a nd K + (Figure 3b) cations,r espectively,t hrough one macrocycle,w hile as andwich-type geometry has been determined for complexation of the bigger K + cations by two 15-crown-5-ethers moieties (Figure 3c). [27] Theh ighly selective transport rate of K + cations is in part due to its sandwich-type recognition by the crown-ethers as observed in the crystal structure,completely surrounding the K + cations in as imilar manner to the water molecules around the hydrated cation (Figure 3c,b ottom).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…[25] Thetransport activity of 1a decreased in the following order: (Table 1), corresponding to the Eisenman sequence IV or V. [26] We know from previously reported X-ray single-crystal structures,t hat lipophilic ureido-benzo-15-crown-5-ether and ureido-benzo-18-crown-6-ether bind Na + (Figure 3a)a nd K + (Figure 3b) cations,r espectively,t hrough one macrocycle,w hile as andwich-type geometry has been determined for complexation of the bigger K + cations by two 15-crown-5-ethers moieties (Figure 3c). [27] Theh ighly selective transport rate of K + cations is in part due to its sandwich-type recognition by the crown-ethers as observed in the crystal structure,completely surrounding the K + cations in as imilar manner to the water molecules around the hydrated cation (Figure 3c,b ottom).…”
Section: Methodsmentioning
confidence: 93%
“…cations (middle and right, black spheres) in the presented X-ray crystal structures. [27] Angewandte Chemie degree of supramolecular order within bilayers.The transport experiments show that these superstructures form membrane spanning structures with clear cation-conductance behaviors. Themacrocycles pointing toward the hydrophylic part of the channel certainly facilitate the transport of the cations, allowing the control of K + -transport selectivity,w hich is rarely observed with self-assembled artificial systems.A s observed in crystal structures,t he dimensional fit of Na + cations induce an incomplete coordination ability,w hich leads,a fter cation entrance,t oapartial dehydration and correspondingly to low transport rate.I nc ontrast, the sandwich-type recognition surrounding the K + cations in asimilar manner to the water molecules around the hydrated cation in water, has important consequences for the highly selective K + translocation along the channel, which totally compensates the energetic cost of their dehydration.…”
Section: Methodsmentioning
confidence: 99%
“…[6] Liposomes, [7] surfaces, [8] dynamers, [9] hybrid materials, [10,11] and mesoporous silica [12] have been used as scaffolding matrices to stabilize and to orient the anisotropic directional G-mesophases. They are reminiscent of other supramolecular pore-confined systems [13,14] or DNA-modified surfaces. [15,16] Among confining matrices, single-layer thin films of mesoporous silicon (pSi), multilayer Bragg reflectors, or Rugate filters can be easily obtained by electrochemical etching (Supporting Information, Figure S1 a).…”
mentioning
confidence: 99%
“…The result is a selfassembled bilayer which exhibits a closer approximation of true cell membrane fluidity [93]. Such a construction also allows for the accommodation of proteins [94], incorporated synthetic ion-channels [95] and sugar lectin systems [96]. Taylor et al has reported on SPR detection of cholera toxin using a tethered bilayer [97].…”
Section: Tethered Bilayersmentioning
confidence: 96%